Metsätalouden kassavirtalaskelma - PackaleŽn, Katja (MTT, 2002)
In this paper a comparison was made for various frameworks used in the Finnish cash flow accouting applicable for forestry. An updating procedure for the forestry cash flow framework was accomplished, so that the latest recommendations given by the Committee of the Corporate Analysis (1999) were met. Data from Finnish bookkeeping farms were used and evaluated in order to find out which of data were suitable for making the cash flow analysis for the forestry. The forestry bookkeeping data and update cash flow framework of forestry were used in order to calculate the cash-based results for the period of 1989-1997. In order to evalute figures on the economical status of forestry in the bookkeeping farms, also some cash-based ratios using the data were formed. The results indicate that at this moment there is no reliable information on some cash-based costs and especially, the asset-values of forestry owned by the farms. Due to this, neither reliable information on cash based return on investment can be received. As a result of this, it would be very important to focus on re-estimating the asset-values of forestry for each bookeeping farm in the future. Only after there-estimation, reliable information on the cash-based, long term profitability of forestry would be available for the farms. Updating and scrutinizing procedure proved the cash analysis to be the most suitable tool for analyzing the economical aspects of forestry with the data employed. Despite some areas of improving, the data used and the cash flow framework utilised in forestry fit well together.
Keywords: Yl; metsätalous; kirjanpitotilat; kassavirta-analyysi; bookkeeping farms; cash flow accounting; forestry accounting